2015
DOI: 10.5935/0103-5053.20150339
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Copper Extraction from Aqueous Sulfate Solution in a Rotating Disc Contactor

Abstract: The extraction of copper from aqueous sulfate solution with new extractant Cupromex-3302 (active substance is the 5-nonylsalicylaldoxime) using a rotating disc contactor (RDC) was investigated. It was observed from batch experiments that the best results were obtained with the initial aqueous pH and concentration of Cupromex-3302 of 1.9 and 10% (v/v) respectively. In continuous experiments, the first critical rotor speed based on drop breakage probabilities was determined. Then the effects of rotor speed, disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The results showed that the operation conditions in the pulsed column with LIX 84-I or Acorga M5640 extractant helped to perform the extraction process with high efficiency ~ 90.5–99.5% 38 , 39 . The utilization of the rotating disc column with the new extractant [Cupromex-3302] for copper separation showed that the process was achieved with maximum extraction efficiency of 87.44% under the operating conditions: 375 rpm, 6.6 L/h, and 8.4 L/h for agitation speed, aqueous flow rate, and solvent organic flow rate, respectively 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the operation conditions in the pulsed column with LIX 84-I or Acorga M5640 extractant helped to perform the extraction process with high efficiency ~ 90.5–99.5% 38 , 39 . The utilization of the rotating disc column with the new extractant [Cupromex-3302] for copper separation showed that the process was achieved with maximum extraction efficiency of 87.44% under the operating conditions: 375 rpm, 6.6 L/h, and 8.4 L/h for agitation speed, aqueous flow rate, and solvent organic flow rate, respectively 40 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, copper ion (Cu 2+ ) is considered as an oxidant of ores (Kasaie et al 2016). It is also used in Fehling liquor destined to determine blood sugar level [8].…”
Section: Introductionmentioning
confidence: 99%